EFFICACY OF AMALGAMATION OF HERBS ON GROWTH AND SURVIVAL OF YOGHURT CULTURE ON FREEZING - DINKER SINGH,; SWASHANKH KUMAR,; JAI SINGH,; AVINASH SINGH, (The Bioscan, 2013)
The present research was planned with an aim to increase the viable count of yoghurt culture and to maintain the viable count in the final product by protecting the yoghurt culture from adverse effect of freezing and subsequent storage at low temperature. The product was fermented with traditional yoghurt culture (Streptococcus salivarius ssp. Thermophilus, Lactobacillus delbrueckii ssp. Bulgaricus) and formulated with different levels of herbal extract at 0.5%, 1.0%, 1.5% and 2.0% for experimental treatment T1, T2, T3 and T4 respectively with 10º Brix. On the basis of selective enumeration, herbal extract with the level of 1.5% in frozen yoghurt has maximum viable count (cfu/g) followed by 1.0%, 2.0% and 0.5%.